Geo-pedological and climatic impact on the distribution and organization of Neolithic settlements in Eastern Croatia (Western Syrmia) - Burić, Marcel; Težak-Gregl, Tihomila (2009)
The work analyzes a sampling of settlement patterns in the extreme eastern periphery of Croatia during the prehistoric period. The layout of present-day settlements from Vukovar to Ilok and the local, very specific relief indicate a degree of mutual interaction. The combination of a series of components such as deep ravines (known locally as surduk) and high loess terraces indicates a unique structure which has been apparent from prehistory to the most recent history.
Projekt MZOS
ENG